Analysis of Risk Control in Broiler Farming Businesses - Fita Rahma Hidayat; M. Oktaviannur (Cita konsultindo, 2024)
The risk that Mr. Taufik Hidayat's broiler farm in Mataram Baru Kec. East Lampung Regency faces is the issue with this thesis. This conversation aims to examine the production and operational hazards that Mr. Taufik Hidayat's broiler farm faces, as well as strategies for mitigating them. The author conducts field research with a descriptive qualitative methodology. methods for analyzing data that include data reduction, data visualization, and conclusion drafting. Data presentation utilizing ISO 31000: 2018, specifically risk treatment (risk control), risk assessment (risk identification, analysis, and evaluation), and context framing. The results of this research indicate that after carrying out the risk management process there were risk events on Mr Taufik Hidayat's broiler chicken farm, Kec. New Mataram District. East Lampung, namely 1 operational risk such as employee negligence, the drinking place is full of husks with a low risk level (low), then 4 production risks such as weather changes with a high-level risk (high), cage density with a medium risk level (medium), chickens experiencing croaking. with a medium level of risk, there is noise with a low level of risk.